Pedicled Transfer of the Superficial Inguinal Lymph Node Flap for Lymphedema - Kung, Theodore A.; Duggan, Nicole M.; Neligan, Peter C. (Journal of Reconstructive Microsurgery Open, 2017)
Background Vascularized lymph node transfer is performed for select patients with lymphedema who remain refractory to nonsurgical therapies. Typically, this involves a microvascular free tissue transfer of donor lymph nodes to the affected area. We describe our experience with the transfer of a pedicled adipofascial flap containing the superficial inguinal lymph nodes for lower extremity lymphedema or penoscrotal lymphedema.Methods In eight patients, a unilateral pedicled superficial inguinal lymph node flap was harvested. The flap consisted of subscarpal adipofascial tissue between the level of the inguinal ligament and the groin crease. Blood supply was from either the superficial circumflex iliac vessels or the superficial inferior epigastric vessels. In certain patients, concurrent lymphaticovenular anastomosis was attempted as well.Results Four patients underwent pedicled superficial inguinal lymph node flap transfer for lower extremity lymphedema and for the other four patients the indication was penoscrotal lymphedema. Seven of the eight study patients reported improvements in their lymphedema symptoms. Postoperative complications included cellulitis in one patient and hematoma in another patient; neither patient required reoperation.Conclusion The pedicled superficial inguinal lymph node flap is a feasible and safe treatment option for either lower extremity lymphedema or genital lymphedema. This case series provides the basis for additional studies regarding the potential use of this vascularized lymph node flap in select patients.
Keywords: lymphedema; vascularized lymph node transfer; lymphaticovenular anastomosis